Kondisi Sanltasi Tempat Penggilingan Daging Dan Kualitas Bakteriologis Daging Bakso Di Pasar Pabaeng-Baeng Kota Makassar - Zaenab Zaenab; Wahyuni Sahani; Mutiara Mutiara (Direktorat Politeknik Kesehatan Makassar, 2024)
Food poisoning cases in Indonesia are still high. The Ministry of Health recorded 81 food poisoning outbreaks in the last three years 2020-2022 with 3,514 cases. Based on the inspection results of the Food and Drug Administration (BPOM) in 2021. The main cause is due to the presence of damaged, expired, and unlicensed products. In addition, other causes are due to poor sanitation practices. This study aims to determine the Sanitation Condition of Meatball Milling Places and the Bacteriological Quality of Meatballs at Pabaeng-Baeng Market, Makassar City. This type of research is descriptive and supported by laboratory examination, the sampling technique used is Total Sampling, the population in this study were all meat mills located in Pabeng-Baeng Market, Makassar City and the samples used were 9 meatball ground dough.The results of this study obtained 7 hyginen of meat milling handlers did not meet the requirements, 9 building conditions did not meet the requirements, and 9 equipment cleanliness did not meet the requirements of PERMENKES No. 1096 of 2011 and in the laboratory examination for Salmonella parameters found that there were 6 samples that were detected positive for Salmonella bacteria did not meet the requirements of SNI 7388: 2009 concerning the Maximum Limit of Microbial Contamination in Food. Based on the results of the study it can be concluded that the processing site items do not meet the requirements and there are samples that are positive for salmonella bacteria. advice given to market managers to pay attention to the sanitary conditions of the processing site. Keywords: Sanitation, Salmonella, Escherichia coli, hygiene.